Effects of oxygen pressure during deposition on the dielectric properties of amorphous titanium dioxide thin films. (25th February 2019) - Elbahri, Marwa Ben; Kahouli, Abdelkader; Mercey, Bernard; Prellier, Wilfrid; Lüders, Ulrike
Abstract: Thin films of TiO2− δ on Si substrates were prepared by pulsed laser deposition for the study of the influence of the O2 growth pressure on their properties, especially the dielectric ones for the integration into MOS capacitances, and the identification of the nature of any excess charges induced by oxygen vacancies. In order to achieve an amorphous growth, low deposition temperatures of 100 °C and 300 °C were chosen. The structure of the films depends on the growth pressure, showing a window of anatase crystalline growth at 300 °C and intermediary growth pressures. The electric and dielectric properties of the films were investigated, and a clear relation between the excess charges produced by oxygen vacancies and the dielectric properties is established. Interestingly, the excess charges do not form small polarons, but are delocalized in the material, leading to high losses for low growth pressures. The optimal growth conditions for the use in capacitances seem to be a growth temperature of 100 °C and a growth pressure of 0.01 mbar, resulting in a dielectric constant of 60 with dielectric losses between 0.2 and 0.002.